Establishment of Modern Universities in Korea - Jeong-Kyu Lee (Arizona State University, 2001)
The purpose of this study is to examine the historical factors which affected the rise of modern higher education during the late Choson period (1880-1910), and to analyze the implications of these historical factors on educational policies in contemporary higher education in Korea. The rise of modern higher education in Korea can be viewed as occurring in three principal phases: Confucian Choson Royal Government, Western Christian missionaries, and patriotic nationalists. The author points out that the major historical factors influencing the development of modern higher education were Confucianism, Christianity, and Korean nationalism. In particular, Confucianism and Christianity have had substantial impacts on the planning of educational policies in contemporary Korean higher education; the former is viewed as an original source of educational enthusiasm which has expanded Korean higher education, and the latter a matrix of modern Korean higher education which has embodied educational enthusiasm.